Pemantapan Kelembagaan Rukun Warga Dan Rukun Tetangga (RT/RW) Di Desa Asrikaton 09 Kecamatan Pakis Kabupaten Malang - Hariyanto, Agoes; Rokhmawati, Dian; Pribadi, Nukhan Wicaksono (Jurnal ABM Mengabdi, 2024)
One of the government partners is Rukun Tetangga (RT) and Rukun Warga (RW). The RT/RW functions as a coordinator between residents, a bridge between the aspirations of fellow residents and the regional government, mediating the resolution of community problems faced by residents, while their duties include helping carry out the Ministry's duties to the community. The government maintains harmony in life, prepares plans and implements development by developing aspirations and pure self-help communities. From the tasks and functions of the RT / RW above, it can be seen that this is a vital task. RT / RW are institutions that are worthy of direct contact with the public, they are the mouths and ears of the Government which have the function of conveying Government policies and being the first recipients of community aspirations. The regional government has issued regulations for the Malang Regency Region number 12 of 2002 concerning RT / RW. However, if we look at the existence of RT/RW institutions in sub-districts that were initiated in carrying out their duties and functions, they are not yet fully implemented. Indicators that appear to be that the RT/RW Chair does not fully know and understand the duties, functions and responsibilities as well as programs managed by the government, the RT/RW organizational structure is not yet functioning well, as well as a lack of good coordination and cooperation between the RT/RW administrator and the government. . Conditions like this have a big impact on the institutional performance of the RT/RW